THE LORENZ SYSTEM SIMULATION. - Sukharev-Chuyan, Maxim (InSight: Rivier Academic Journal)
The Lorenz system is discussed as a simple basic model of chaotic behavior. Java code for an animation of the waterwheel model of the Lorenz system is included. The simulation demonstrates chaotic behavior of the numerical solution of the Lorenz' system of nonlinear ordinary differential equations.